Joint mechanical characteristics of vertical jumping in elite sprinters - Zhang, Wangli; Liu, Chaopan; Bai, Yijun; Liu, Qiqi; Cui, Cui (Molecular & Cellular Biomechanics, 2024)
This study aims to investigate the key lower limb joint biomechanical factors affecting the performance of vertical jumping in high-level sprinters, focusing on analysing the torque, power output and stiffness of the hip, knee and ankle joints during the vertical jumping process. The relationship between the joint biomechanical parameters and the key indexes of vertical jump performance, including ground contact time, free height and reaction power index, was systematically analysed through the simultaneous acquisition of 3D kinematic and kinetic data of the sprinters. The results showed that different lower limb joints play key roles in different phases of the long jump. During the centrifugal phase (landing), knee stiffness had a significant effect on ground contact time, with athletes with greater stiffness demonstrating shorter contact times, thus contributing to a quicker entry into the centripetal phase (jumping). In contrast, during the centripetal phase, ankle power output was highly correlated with free height and explosive performance, showing the decisive role of the ankle joint in vertical mobility at the start of the jump. The hip joint also plays a role in coordinating upper and lower limb movements and enhancing power transfer throughout the exercise process, but its influence is more indirect. This study provides biomechanical empirical evidence for the training of sprinters, especially by enhancing knee joint stiffness and ankle joint power output, athletes can effectively improve the performance of vertical jump manoeuvres. These findings provide a scientific basis for coaches and athletes to optimise their training programmes and improve their performance in competitions, and provide a reference direction for future related research.